Raman scattering studies on single-crystalline bulk AlN under high pressures - Kuball, M.; Hayes, J. M.; Prins, A. D.; Van Uden, N. W.; Dunstan, D. J.; Shi, Ying; Edgar, James H. (My University, 2001)
We report on the Raman analysis of wurtzite single-crystalline bulk AlN under hydrostatic pressures up to 10 GPa. The pressure dependence of the AlN phonon frequencies was investigated. Mode Gru¨neisen parameters of 1.39, 1.57, 1.71, 0.93, and 1.26 were determined for the A₁ (TO), E₁ (TO), E₂ (high), A₁ (LO), and the quasi-longitudinal optical phonons, respectively. Recent theoretical calculations underestimate the pressure-induced frequency shift of the AlN phonons by about 20%–30%. Mode Gruneisen parameters of AlN were compared to those of GaN.
Keywords: Aluminum nitride; GaN; Spectroscopy; Strain; Layers; Volume